Synthesis and Characterization of MgO Doped ZnO Nanorods Prepared by Solution Immersion Method and their Effect on Energy Band Gap - Khusaimi, Z; A.M. Asib, N; Z. Umbaidilah, S; N. Afaah, A; N.E. Syafika, C; F. Chayed, N.; Rusop, M. (International Journal of Engineering and Technology, 2019)
In this research, solid powder form ZnO and MgO-doped ZnO were prepared by using solution immersion method. Mg divalent cation with different atomic percentage of 0.5%, 1.0% and 1.5% were added in 0.04 M of Zn2+ solution containing zinc nitrate hexahydrates as precursor and hexamethylene tetraamine as stabilizer. Annealing treatment was consequently carried out to transform the precursors into oxide forms. ZnO and MgO-doped ZnO were successfully obtained and the surface morphology, crystallite size and elemental composition were studied using Field Emission Scanning Electron Microscope (FESEM) and Energy dispersive X-Ray (EDX) respectively. The band gap energy was determined using Ultraviolet-Visible spectrophotometer (UV-Vis). FESEM images showed that the powder form of ZnO and MgO-doped ZnO consist of rod-like shape. A 0.5% of MgO-doped ZnO sample has smallest size of rods with higher aspect ratio compared to others. The EDX result revealed that the sample composed of Zn, O and Mg in the sample. The band gap energy for all samples was determined using Tauc plot and it was found that the band gap energy is reduced with 1.0 and 1.5 % doping while increased at 0.5% doping. The band gap energy was found to range between 3.23 eV to 3.26 eV. The 0.5% of Mg-doped ZnO with higher aspect ratio shows the highest band gap energy value.Â Â